MEGA MARKETING BANK SYARIAH - Putri, Galuh Nadiya; Fasa, Muhammad Iqbal; Suharto, Suharto (STAI Darul Qalam Tangerang, 2024)
Marketing is a significant aspect to increase consumer trust. Hence, it is essential to educate the consumer with the lesson of the importance of syarî’ah products concerning the marketing aspects. In fact, many banks serves the custo mer with syariah service in Indonesia. The basic concept of spiritual marketing is the, and loyality to Allâh swt. The key of ethics and moral of managements of creation, taste, heart and work (the implementation). Those concepts are under the guidence of faith integrity, obidience business is truly placed on the doers. A Muslim busines manager must hold tightly the ethic and moral of business that cope –khusn al-huluq, trusty, dan tolerant. There are three marketing strategies of syariah banking; marker driven strategic, viral marketing way, and fish net strategy. Element of mega marketing that had been intruduced by Rasûlullâh since the fifteenth century, and now can be adopted to any kinds of businesses including syariah banking